Magnetic characterization of solid food to gastric emptying studies by mechanical-magnetogastrography assessment - Córdova-Fraga, Teodoro; Rodríguez, D.; De la Roca-Chiapas, J. M.; Sosa, M.; Hernández, M. A.; Vargas, M.; Solorio, S. E.; Bernal, J. J. (Revista Mexicana de Ingenieria Biomedica, 2011)
Mechanical-Magnetogastrography (M-MGG) is a technique that has been used to measure gastric emptying in healthy subjects and patients with gastrointestinal pathologies. This has allowed implementing a non-invasive technology, free of ionizing-radiation and it may be used in diagnostic tests in clinical medicine. The characterization of a phantom which has a magnetic behavior similar to that observed in gastric emptying studies carried out in persons is presented. A fluxgate magnetometer was used to record the signal in a magnetic unshielded room. Phantom included nine identical deposits prepared with magnetite, Fe3O4 and flour. The behavior of the experiment is identical to studies previously reported in evaluations of healthy people and patients.